2007
DOI: 10.1542/peds.2006-1205
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Steps for Young Children: Sustained Results at 5.5 Years

Abstract: Sustained treatment effects, albeit modest, are consistent with early findings. Universal, practice-based interventions can enhance quality of care for families with young children and can improve selected parenting practices beyond the duration of the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
121
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(122 citation statements)
references
References 32 publications
0
121
1
Order By: Relevance
“…13,[36][37][38] In a recent review of tools and strategies to improve WCC, we found evidence suggesting that inclusion of nonphysician providers into a health care team could improve receipt of anticipatory guidance and developmental and behavioral services. 16,17,[39][40][41][42] In Healthy Steps, a physician and child developmental specialist (typically a nurse, social worker, or early childhood educator) provide WCC in partnership. In a large, national, 3-year trial, intervention parents reported receiving more anticipatory guidance and more family-centered care and were more likely to be up-to-date on WCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[36][37][38] In a recent review of tools and strategies to improve WCC, we found evidence suggesting that inclusion of nonphysician providers into a health care team could improve receipt of anticipatory guidance and developmental and behavioral services. 16,17,[39][40][41][42] In Healthy Steps, a physician and child developmental specialist (typically a nurse, social worker, or early childhood educator) provide WCC in partnership. In a large, national, 3-year trial, intervention parents reported receiving more anticipatory guidance and more family-centered care and were more likely to be up-to-date on WCC.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[12][13][14][15] Various tools and strategies to redesign the structure of WCC have been proposed and studied; however, there are few evidencebased comprehensive models of care to serve as feasible and sustainable alternatives to the current WCC structure in most small community practices. 16,17 Our comprehensive model (ie, the Parentfocused Redesign for Encounters, Newborns to Toddlers [PARENT]) was developed to address these key structural deficiencies in our current WCC system by decreasing reliance on the physician for routine WCC and shifting many WCC services to a health educator. 18 Our objective was to test the effectiveness of the PARENT intervention in providing comprehensive, nationally recommended WCC services, while optimizing WCC, urgent care, and emergency department (ED) utilization among low-income families.…”
mentioning
confidence: 99%
“…Reach Out and Read, Video Interaction Project, and Healthy Steps are innovative examples of existing programs that have shown promise in leveraging the primary care office to support positive parenting practices. [40][41][42][43][44][45] Additional strategies that increase interactive parenting practices in vulnerable families that are brief and workable into a busy pediatric clinic will be an important area for future research and public health initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy Steps for Young Children, a manual-based primary care strategy, and programs such as Incredible Years and Triple P, which integrate behavioral health into primary care, have been shown to promote responsive parenting and address common behavioral and developmental concerns. [69][70][71][72][73] Early literacy promotion in the medical home with programs such as Reach Out and Read advances reading readiness by approximately 6 months when compared with controls. 74 In addition, parents in Reach Out and Read practices are 4 times as likely to read to their children and more likely to spend time with their children in interactive play 75 than are families who are not in Reach Out and Read.…”
Section: Family and Parenting Support In The Medical Homementioning
confidence: 99%